OPTIMIZING THE PERFORMANCE OF WIND TURBINES USING EXHAUST GAS AT THE BORANG GAS POWER PLANT - Fitrianza; Arifin, Fatahul; RS, Carlos (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2025)
As a renewable energy source, wind energy is one of the promising energies to be developed using wind turbines. The wind source to drive wind turbines comes from natural wind sources and exhaust wind from equipment. Palembang is one of the provinces in Indonesia with relatively low wind energy potential, with an average wind speed ranging from 1.5 to 3 m/s. However, at the PLTG Sematang Borang power plant owned by PT PLN, there is equipment that produces exhaust wind with a speed of 5 m/s. This study will compare the performance of Horizontal Axis Wind Turbines (HAWTs) and Savonius Vertical Axis Wind Turbines (VAWTs) to design wind turbines that can meet power generation needs and reduce operational power consumption.